Dietary patterns and practices in rural eastern Uganda: Implications for prevention and management of type 2 diabetes. (1st December 2019) - Kiguli, Juliet; Alvesson, Helle Mölsted; Mayega, Roy William; Kasujja, Francis Xavier; Muyingo, Anthony; Kirunda, Barbara; Ekirapa Kiracho, Elizabeth; Kayemba Nalwadda, Christine; Naggayi, Gloria; Peterson, Stefan; van Olmen, Josefien; Daivadanam, Meena
Abstract: Background: The burden of type 2 diabetes in Sub-Saharan Africa is projected to double by 2040, partly attributable to rapidly changing diets. In this paper, we analysed how community members in rural Uganda understood the concept of a healthy or unhealthy diet, food preparation and serving practices to inform the process of facilitating knowledge and skill necessary for self-management and care for type 2 diabetes. This was a qualitative study involving 20 focus group discussions and eight in-depth interviews among those at risk, patients with type 2 diabetes and the general community members without diabetes mellitus. Data was coded and entered into Atlas ti version 7.5.12 and interpreted using thematic analysis. We identified three main themes, which revealed, the perceptions on food and diet concerning health; the social dimensions of food and influence on diet practices; and food as a gendered activity. Participants noted that eating and cooking practices resulted in unhealthy diets. Their practices were affected by beliefs, poverty and food insecurity. Women determined which foods to prepare, but men prepared only some of the foods such as delicacies like a rice dish " pilau ." New commercial and processed foods were increasingly available and consumed even in rural areas. Participants linked signs and symptoms of illness to diet as they narrated changes from past to current food preparation behaviours. Their view of overweight and obesity was also gendered and linked to social status. Participants' perception of disease influenced by diet was similar among those with and without type 2 diabetes, and those at risk. People described what is a healthy diet was as recommended by the health workers, but stated that their practices differed greatly from their knowledge. There was high awareness about healthy and balanced diets, but food is entrenched within social and gendered paradigms, which are slowly changing. Social and gender dimensions of food will need to be addressed through interventions in communities to promote change on a society level.